Generation and characterization of polyclonal antibodies specific to N-terminal extension of p85 isoform of ribosomal protein S6 kinase 1 (p85 S6K1) - Savinska, L.O.; Klipa, O.M.; Khoruzenko, A.I.; Shkarina, K.A.; Garifulin, O.M.; Filonenko, V.V. (Вiopolymers and Cell, 2015)
Aim. Generation of polyclonal antibodies specific to the ribosomal protein S6 kinase isoform – p85S6K1 and directed to the N-terminal (1–23 aa) extension of p85S6K1. Methods. Animal immunization with synthetic (1–23 aa) peptide, ELISA, Western blot, Immunoprecipitation, immunofluorescent analysis. Results. Polyclonal antibodies have been generated, which specifically recognize only p85 but not p70 isoform of S6K1 in western blot, immunoprecipitation and immunofluorescence analysis. Conclusions. The obtained antibodies can be recommended for studies on the p85S6K1 and other S6K1 isoforms possessing the N-terminal extension – the identification of binding protein partners, analysis of subcellular localization under different physiological conditions, elucidation of the signal transduction pathways involving different S6K1 isoforms. Мета. Отримати поліклональні антитіла специфічні до p85 ізоформи S6K1 и спрямовані до N-кінцевого (1–23 a.к.) подовження p85S6K1. Методи. Іммунизація тварин синтетичним (1–23 а.к.) пептидом, ІФА, вестерн блот, іммунопреципітація, іммуноцитохимічний аналіз. Результати. Отримано поліклональні антитіла, що розпізнають p85, але не p70 ізоформу S6K1 в вестерн блот анализі, іммунопреципітації і іммуноцитохімичному аналізі. Висновки. Отримані антитіла можуть бути рекомендованими для дослідження p85S6K1 та інших ізоформ S6K1, що мають N- кінцеве подовження – ідентифікації білків-партнерів, аналізу субклітинної локалізації за різних фізіологічних умов, аналізі ролі S6K1 ізоформ в сигнальній трансдукції. Цель. Получить полииклональные антитела специфичные к p85 изоформе S6K1 и направленные против N-концевого (1–23 a.к.) удлинения p85S6K1. Методы. Иммунизация животных синтетическим (1–23 а.к.) пептидом, ИФА, вестерн блот, иммунопреципитация, иммуноцитохимический анализ. Результаты. Получены поликлональные антитела распознающие p85, но не p70 изоформу S6K1 в вестерн блот анализе, иммунопреципитации и иммуноцитохимическом анализе. Выводы. Полученные антитела могут быть рекомендованы для изучения p85S6K1 и других изоформ S6K1 обладающих N-концевым удлинением – идентификации белков партнеров, анализе субклеточной локализации при разных физиологических условиях, анализе роли S6K1 изоформ в сигнальной трансдукции.